Exploring TEIA: Designing Musical Textures for Live Electronic Music - Antunes, Micael (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This article presents TEIA (Stochastic Textures with Assisted Interaction), a Max tool developed for real-time texture generation in the composition Gestos: uma homenagem a Jaques Morelenbaum. The tool is inspired by György Ligeti’s metaphor of spider webs, used to explore the notion of texture in composition. TEIA treats musical texture as a high-level perceptual phenomenon shaped by the interrelationships of sound components, focusing on their density, variety, and interactions. Drawing on psychoacoustic and compositional analyses of Ligeti and Xenakis, the tool generates complex sonic textures through pitch shifter configurations that manipulate sound masses. The article begins by discussing the creative context and compositional influences behind Gestos, exploring the intersection of composition, perception and computer music. It then delves into the design and functionality of the tool, highlighting its core textural behaviours, audio descriptors, and PCA-based analysis. Finally, the article reflects on the potential of TEIA to enable real-time manipulation of sound texture, thus contributing to the ongoing dialogue between composition, technology and perception.